2021
DOI: 10.1021/acssuschemeng.0c09241
|View full text |Cite
|
Sign up to set email alerts
|

Enabling LiNi0.88Co0.09Al0.03O2 Cathode Materials with Stable Interface by Modifying Electrolyte with Trimethyl Borate

Abstract: As one of the most promising cathode materials in lithium-ion batteries, nickel-rich cathode materials have been widely studied due to their high specific capacity and high operating voltage to realize the energy density of 300 Wh kg −1 . However, the oxidative decomposition of electrolyte catalyzed by transition metal ions and the crack of secondary particles have brought great challenges to their further development. In order to solve this problem, functionalized electrolyte is often used to stabilize the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…For the fresh GPE-ZIF8-Al 2 O 3 film, the main signal of F 1s located at 687.2 eV is from C–F bonds of PVDF-HFP, and the shoulder peak that appeared at 684.6 eV can be well-attributed to Zn–F bonds, suggesting there is a strong interfacial interaction between the ZIF-8 layer and polymer matrix . The signals of C 1s located at 284.8, 285.6, 286.8, and 289.1 eV are assigned to C–C, C–H, C–O, and CO bonds of ZIF-8 and CA, respectively . Moreover, the single peak of Al 2p of Al 2 O 3 appears at 74.4 eV .…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…For the fresh GPE-ZIF8-Al 2 O 3 film, the main signal of F 1s located at 687.2 eV is from C–F bonds of PVDF-HFP, and the shoulder peak that appeared at 684.6 eV can be well-attributed to Zn–F bonds, suggesting there is a strong interfacial interaction between the ZIF-8 layer and polymer matrix . The signals of C 1s located at 284.8, 285.6, 286.8, and 289.1 eV are assigned to C–C, C–H, C–O, and CO bonds of ZIF-8 and CA, respectively . Moreover, the single peak of Al 2p of Al 2 O 3 appears at 74.4 eV .…”
mentioning
confidence: 97%
“…50 The signals of C 1s located at 284.8, 285.6, 286.8, and 289.1 eV are assigned to C−C, C−H, C−O, and CO bonds of ZIF-8 and CA, respectively. 51 Moreover, the single peak of Al 2p of Al 2 O 3 appears at 74.4 eV. 52 On the one side, after the system is cycled for 1000 h, the main signal of F 1s of GPE-ZIF8-Al 2 O 3 appears at 685.0 eV, and a single peak for Li 1s, meanwhile, rises at 55.6 eV, clearly declaring the formation of LiF.…”
mentioning
confidence: 99%
“…In contrast, the cathode prepared via the co-precipitation method delivered only 130.3 mA h g À1 after 100 cycles, with a capacity retention of 63.31%. Xiao et al 81 reported the synthesis of an LiNi 0.88 -Co 0.09 Al 0.03 O 2 cathode with the addition of trimethyl borate (TMB) in the commercial electrolyte, which enhanced the interfacial stability. The LiNi 0.88 Co 0.09 Al 0.03 O 2 electrode with 10% TMB-containing electrolyte could achieve a capacity retention of up to 82% after 300 cycles at 1C rate (1C = 200 mA h g À1 ).…”
Section: Electrodes For Li-ion Batteriesmentioning
confidence: 99%
“…Li-ion batteries are the most popular rechargeable power source for portable electronics and electric vehicles due to their relatively high energy density. To seek further improvement in energy density, Ni-rich layered oxides such as LiNi x Co y Mn z O 2 ( x ≥ 0.6) are considered to be one of the most promising cathode materials for Li-ion batteries in the near future. Normally, the higher the Ni content of Ni-rich cathode materials, the higher the capacity. However, the higher Ni content in Ni-rich cathode materials poses more serious challenges in terms of surface slurrying, structural deterioration, interfacial parasitic reaction, and mechanical cracking, in which the structural degradation initiating at the surface and extending to the bulk inherently leads to the sluggish lithium-ion diffusion and, thereby, the worsened electrochemical performance, causing the rapid decay of capacity and potential. , Therefore, surface modification is usually used to improve the cycle stability of Ni-rich cathodes. On the surface of cathodes, electrolyte decomposition occurs upon cycling because of oxygen evolution of the highly delithiated cathodes to inevitably form a cathode/electrolyte interface (CEI) layer whose properties such as conductivity of Li-ion and stability can influence the strong electrochemical performance of the cathodes. The nonuniform coverage of the CEI leads to transition metal dissolution and surface structural degradation of the Ni-rich cathode materials because of the uneven lithium transport rate across the interface . In addition, hydrofluoric acid resulting from lithium hexafluorophosphate decomposition attacks the surface to leach transition metal out from the oxide structure, accelerating surface reconstruction .…”
Section: Introductionmentioning
confidence: 99%